Modular Forms and Fermat’s Last Theorem 1997
DOI: 10.1007/978-1-4612-1974-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Construction of Universal Deformation Rings

Abstract: Abstract. Let V be an absolutely irreducible representation of a profinite group G over the residue field k of a noetherian local ring O. For local complete O-algebras A with residue field k the representations of G over A that reduce to V over k are given by O-algebra homomorphisms R → A, where R is the universal deformation ring of V . We show this with an explicit construction of R. The ring R is noetherian if and only if H 1 (G, End k (V )) has finite dimension over k. IntroductionLet G be a profinite grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 6 publications
(6 reference statements)
0
82
0
Order By: Relevance
“…By a result of Faltings (see [18,Prop. 7.1]), V has a universal deformation ring in case End kG (V ) = k.…”
Section: Universal and Versal Deformation Ringsmentioning
confidence: 99%
See 2 more Smart Citations
“…By a result of Faltings (see [18,Prop. 7.1]), V has a universal deformation ring in case End kG (V ) = k.…”
Section: Universal and Versal Deformation Ringsmentioning
confidence: 99%
“…Let Γ be a profinite group, and suppose V is a finite dimensional vector space over k with a continuous Γ-action. If all continuous kΓ-module endomorphisms of V are given by scalar multiplications, an argument of Faltings (see [18]) shows that V has a universal deformation ring R(Γ, V ). The topological ring R(Γ, V ) is universal with respect to deformations of V over commutative local W -algebras with residue field k which are the projective limits of their discrete Artinian quotients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, R(G, V ) represents the functor F V in the sense that F V is naturally isomorphic to Hom C (R(G, V ), −). For more information on deformation rings see [13] and [19].…”
Section: Preliminariesmentioning
confidence: 99%
“…[12], [21,20], [9] and their references). In [13], de Smit and Lenstra showed that if Γ is an arbitrary profinite group and V is a finite dimensional vector space over k with a continuous Γ-action which has a universal deformation ring R(Γ, V ), then R(Γ, V ) is the inverse limit of the universal deformation rings R(G, V ) when G runs over all finite discrete quotients of Γ through which the Γ-action on V factors. Thus to answer questions about the ring structure of R(Γ, V ), it is natural to first consider the case when Γ = G is finite.…”
Section: Introductionmentioning
confidence: 99%